Response of human periodontal ligament stem cells to IFN-γ and TLR-agonists. Issue 1 (December 2017) - Andrukhov, Oleh; Hong, Johanna; Andrukhova, Olena; Blufstein, Alice; Moritz, Andreas; Rausch-Fan, Xiaohui
Abstract Periodontal ligament stem cells similarly to the mesenchymal stem cells of other tissues possess immunomodulatory properties, which are regulated by different cytokines, particularly by interferon-γ (IFN-γ). In contrast, less information is provided about the effect of toll-like receptors ligand on immunomodulatory properties of these cells. In the present study we investigated the response of human periodontal ligament stem cells (hPDLSCs) in response to simultaneous stimulation with IFN-γ and toll-like receptor (TLR) agonists. The resulting expression of indoleamine-2, 3-dioxygenase-1 (IDO-1), interleukin (IL)-6, IL-8 and monocyte chemotactic protein 1 (MCP-1) was investigated. The expression of IDO-1 was upregulated by IFN-γ in both gene and protein levels. TLR2 agonists Pam3CSK4 induced gene expression of IDO-1, but had no effect on protein expression. IFN-γ induced IDO-1 protein expression was further enhanced by Pam3CSK4. TLR-4 agonistE. coli LPS has no significant effect on neither basal nor IFN-γ induced IDO-1 protein expression. The production of IL-6, IL-8, and MCP-1 was induced by TLR agonists. Neither basal nor TLR agonists induced production of these proteins was affected by IFN-γ. Our data shows potential interaction between IFN-γ and TLR2 responses in hPDLSCs, which might be involved in regulation of immune response in inflammatory diseases, and particularly periodontitis.